Perspektywy rozwoju dobrowolnych form oszczędzania w polskim systemie emerytalnym - Mosionek, Magdalena (The Prospects Of Voluntary Pension Sayings Expansion in the Polish Pension System, 2008)
Occupational Pension Programme were introduced to the Polish pension system in 1999 as a supplement of basic, universal parts of this system. In September 2004, abreast the Occupational Pension Schemes, there were implemented Individual Pension Accounts - and despite the fact that these pension savings forms are of voluntary character, they should be treated as an essential part of the Polish pension system. The development of this part of capital pension system is necessary because of the very low level of predicted replacement rate. The aim of this paper is to present the hitherto functioning of Occupational Pension Schemes and Individual Pension Accounts as well as to point out the foreseen prospects of their development in the tore stated on the basis of the results of questionnaire survey carried out among representatives of life insurance companies and investment fund companies - financial institutions which offer pension schemes and individual sayings accounts in third additional pillar of the Polish pension system.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1197, s. 286-293